Study on Primary Adrenal Insufficiency (PAI): Experience in a Major Teaching Hospital, Riyadh, Saudi Arabia - Al-Jurayyan, N. A. (New Frontiers in Medicine and Medical Research Vol. 10, 2021)
Background: Primary adrenal insufficiency (PAI) in children is an uncommon, but potentially fatal. The current symptoms include weakness, fatigue, anorexia, abdominal pain, weight loss, orthostatic hypotension, salt craving and characterized by hyperpigmentation. Aims: The objective of this study was therefore, to define the etiology of PAI in a large referral, teaching hospital in Riyadh, Saudi Arabia. Materials and Methods: This is a retrospective, hospital based-study, conducted at King Khalid University Hospital (KKUH), during the period January 1989 and December 2014. Review of medical record of patient diagnosed with pri- mary adrenal insufficiency. The diagnosis was based on medical history, physical examination and low levels of glucocor- ticoids and raised adrenocorticotropic hormone (ACTH). Appropriate laboratory and radiological investigations were also reviewed. Results: During the period under review, January 1989 and December 2014, a total of 125 patients with the diagnosis of primary adrenal insufficiency were seen. Inherited disorders like congenital adrenal hyperplasia and hypoplasia were com- mon, 85.5%. However, variable autoimmune mediated etiologic diagnosis accounted for, 13%, were also seen. The appro- priate various laboratory and radiological investigations should be planned. Conclusion: Although, congenital adrenal hyperplasia was the commonest etiology, however, congenital adrenal hypoplasia should not be over looked. The diagnosis of PAI can be challenging in some patients, and therefore appropriate serological.